FACES DA FEIURA NA ESCRITA DE AUTORIA PARANAENSE - Valério, Maristela Scremin (2014)
Since the first images drawn on the caves walls of prehistoric man, the figure of the woman has always caused fascination. It is not from today they are judged by appearance. Umberto Eco (2007) points out that as the feminine beauty was associated with seduction and sin, ugliness was also considered a danger. Among women condemned to the Inquisition flames, it had one thing in common: ugliness. In contemporary times, with the imagery society advent, beauty, youth and health become inseparable synonymous. The beauty in our time, is something to be built, shaped, bought. The ugliness, then, it is related to laziness, carelessness and lack of persistence. Beauty is the reward for the effort and discipline. Whereas the literature deals with reality representations, the purpose of this dissertation is to understand how the ugliness is portrayed through intimate literature of some women writers. For this, this research was to Paraná contemporary writers. After search, they were chosen the works of writers Luci Collin and Regina Benitez for the continuation of this work. Through selected stories, we intend to discuss about the aesthetic ideals that influence the lives of contemporary women. The analysis is based in cultural studies, gender studies and concepts of Roger Chartier representation.